Learning from the unfamiliar: How does working with people who use mental health services impact on students' learning and development?. Issue 3 (3rd April 2018) - Asghar, Mandy; Rowe, Nick
Abstract: Service learning is an experiential pedagogic approach that is predicated on students learning in authentic situations. It is often problem-orientated and provides opportunities for community engagement in ways that enhance a student's capacity as a socially aware individual. There is evidence that such learning opportunities can enhance personal development, team and collaborative skills as well as improve self-confidence. This article reports on a qualitative research project that explored the experience of a group of students who worked in a service learning project with users of mental health services. Using the lifeworld as a means to analyse the data provided a rich description of the impact it had on their learning. Three themes are portrayed: being together, encounters in the real world, and becoming. Important aspects of the findings include: the opportunity to learn without the constraint of pre-determined learning outcomes, learning through uncertainty and learning from those who are different and unfamiliar. Considering the data from the perspective of a Jarvis's learning theory, we explore how particular situations stimulated disjuncture, those uncomfortable moments that instigate learning. The article concludes by highlighting the benefits of a tight–loose design to pedagogic approaches, and emphasising how learning from those who are different provides students with opportunities to engage with the messiness of the real world.